Bike-Sharing: Network Efficiency and Demand Profiles - J. Ignacio Gimenez-Nadal; Carlos Gracia-Lazaro; José Alberto Molina (Institute of Labor Economics (IZA), 2021)
This paper analyzes a bike-sharing service from both network efficiency and demand profiles perspectives. Specifically, it focuses on the BIZI service in the city of Zaragoza (Spain), which was launched in May 2008 with the aim of increasing the use of the bicycle in the city. Since then, the number of users has increased smoothly, and the service currently constitutes an integrated transport mode as an alternative to the use of cars and public transport in the city. The paper analyzes the evolution of the use of the BIZI service, using network analysis to show that efficiency increased rapidly over time until reaching an optimum value after two years. Furthermore, using regression models the paper characterizes the groups that most use this service, and relates service demand to factors such as weather conditions, number of bike lanes, and service extensions. This analysis will allow us to characterize the demand for this service, which can be of great importance when developing integrated transport payment systems.
Keywords: R40; C45; 330; BIZI service; efficiency; weather conditions; socio-demographic characteristics; bike lanes; bike stations